Exposure to high-frequency transient electromagnetic fields - Skotte, Jørgen H. (Scandinavian Journal of Work, Environment & Health, 1996)
' ' OBJECTIVES ': 'The purpose of this study was to assess exposure to high-frequency transient (HFT) electromagnetic fields in occupational and residential environments.' ' METHODS ': 'Exposure to HFT electromagnetic fields was measured with personal dosimeters for 301 volunteers (396 measurements) in periods of 24 h in both occupational and residential environments. The study included electrical utility workers (generation, transmission, distribution, substation), office and industrial workers, and people living near high-power transmission lines. The measure of exposure to HFT fields was specified as the proportion of time (parts per million) in which the electric field exceeds a nominal threshold level of 200 V·m-1 at 5–20 MHz. Recently the specification of the HFT channel of the dosimeter has been found to be incomplete; therefore a testing of the threshold level and the sensitivity to electromagnetic fields from radio-telephones was carried out.' ' RESULTS ': 'The percentage of measurements with a mean workday exposure above 0.1 ppm was 6.5–9.4% for the utility groups and 0.9% for all the nonwork measurements. It is likely that the use of radio-telephones has contributed significantly to the number of HFT events in some of the measurements, especially for the generation workers. The nominal threshold level of the dosimeter was found to vary considerably depending on the polarization of the field (20–400 V·m-1 at 13.56 MHz for one instrument).' ' CONCLUSION ': 'Generally speaking, HFT fields appeared infrequently. The workday exposure to HFT fields and 50 Hz magnetic fields ranked the groups differently. There is a need for developing instrumentation for HFT field measurements further.
Keywords: HFT field; high-frequency transient field; occupational environment; pulsed electromagnetic field; radio-telephone; residential environment; utility industry